"Little man you've had a busy day": Music in the onstage and offstage lives of "Master Harold". (June 2022) - Fourie, Paula
Frequently referred to by its characters, and often approximated or imagined by them, music plays an important — if largely unacknowledged — role in Athol Fugard's "Master Harold" … and the Boys . This play is widely considered one of Fugard's most obviously autobiographical works, the setting and characters based on the places and people that defined his Port Elizabeth youth. This article explores a further congruence between the playwright's (auto)biography and this play, namely the role of music in each. As we learn from his autobiographical texts, Cousins: A Memoir (1997) and Notebooks: 1960–1977 (1983), listening to and trying to make music have constituted important activities in Fugard's lived experience, most notably during his childhood and youth. Consequently, music holds a particular currency for Fugard. This article argues that Fugard entertains a perception of music as a privileged form of creative expression rooted in his own unfulfilled desire to make music. It also argues that these attitudes are reflected in the symbolic power afforded to music in "Master Harold" … and the Boys, informing a tension in the play between the presence of music and, conversely, the absence thereof. Through exploring music in the onstage and offstage lives of Master Harold, this article offers a reading that reconciles the autobiographical dimensions of the play with its political significance. Doing so has particular consequences for reading the absence of Hally — Fugard's fictional avatar — from the play's final, tantalizing, image of a non-racial South Africa.